(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Preambolo - 2. La potenza delle parole - 3. La forza di un sentimento - 4. Inventarsi la verità - 5. La desacralizzazione di Dio - 6. La sacralizzazione dell’uomo - 7. Epilogo. Quo Vadis: A Narrative of the Time of Nero. The Power of the Words ABSTRACT: Set during the reign of the emperor Nero, Quo Vadis tells the story of the love that develops between a young Christian woman and a Roman officer who, after meeting her fellow Christians, converts to her religion. Underlying their relationship, the novel becomes a good stratagem to emphasize the contrast between the worldly opulence of the Roman Empire and the poverty and spiritual power of the Christians, whose concepts would play a crucial role during the long history of the Western Legal System. With this paper the Author tries to explain how important a novel like Quo Vadis could be in order to better understand the strong impact of the Christian tradition on the history of Western constitutionalism.